Tantangan dan Peluang Pemberdayaan UMKM di Indonesia: Antara Regulasi, Akses Permodalan, dan Digitalisasi - Sholikin, Ahmad (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
MSMEs are the backbone of Indonesia’s economy, playing a pivotal role in job creation and economic growth. However, empowering these enterprises still faces numerous challenges, particularly in the areas of complex regulations, limited access to capital, and rapid digital transformation. This study aims to identify and analyze the challenges and opportunities encountered by MSMEs in Indonesia, focusing on government policies, capital availability, and the implementation of digital technologies. Employing a qualitative approach that includes literature review, policy analysis, and in-depth interviews with MSME stakeholders, the findings reveal that fragmented and insufficiently integrated regulations often create bureaucratic obstacles, hindering innovation and business expansion. Moreover, limited access to capital poses significant difficulties for MSMEs, especially during the early stages of business development. Conversely, digitization offers considerable opportunities by expanding market access, enhancing operational efficiency, and providing innovative financial solutions. These insights underscore the necessity for a synergistic approach that combines regulatory reform, improved funding mechanisms, and the adoption of digital technologies to maximize the empowerment of MSMEs. The study recommends fostering cross-sectoral collaboration among government agencies, financial institutions, and industry stakeholders to create a conducive ecosystem for sustainable MSME growth in the digital era.